Grand Theater Urbanism Chinese Cities in the 21st century - Xue, Charlie Qiuli; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This volume explores the phenomenon and trend of cultural buildings by investigating 10 typical cities in China from the first, second, and third tiers, and from the Chinese diaspora. Each grand theater design was the result of a high-profile international competition and created by global architects in collaboration with Chinese design institutes. The national and international significance of these iconic projects lies in the fact that they not only reflect the dynamics of global design ideas, but also represent a particular historical moment in China's modernization process. The development, histories, and purposes of constructing cultural buildings are carefully outlined and colorfully presented. Given China's tremendous population, the development trajectory of its urban construction will provide insights for other regions that hope to embark on the high-speed track in the 21st century. "In 'Grand Theater Urbanism', Professor Charlie Xue and his team document China's current shift towards a culture of consumption and leisure, symbolized by the construction of multi-use Grand Theaters in major cities. 'Grand Theater Urbanism' reveals the unexpected variety and complexity of this contemporary cultural drive in a series of exemplary chapters with highly detailed, local, case studies." --Professor David Grahame Shane, Columbia University, New York "Jane Jacobs likened city life to a performance. This book goes a stage further and analyses the actual performance spaces within cities in China. In doing so it makes a valuable connection between urban design and the cultural life in cities. This is an important and often forgotten dimension of urbanism and I heartily commend this book to readers.'" --Professor Matthew Carmona, The Bartlett, University College London.
Preface and acknowledgments -- Introduction: City Branding and Cultural Facilities-boosting Chinese cities -- Development of Theaters and the City in Beijing: the 1950s and After the 1980s -- To Be Cultural Capital-grand theaters in Shanghai -- Guangzhou Opera House: Building a Gated Public Space -- City Center Shifting and Cultural Facilities - Performance Space in Shenzhen -- Growing with the City: Theatrical Buildings in Chongqing -- The Henan Art Center: From Dilemma to Ambition -- The Shanxi Grand Theater: "Renaissance" of Chinese Drama Land -- A Butterfly by the Lake - Wuxi Grand Theater -- The National Taichung Theater: experimenting publicity of metropolitan urbanism -- From Colonial to Global-performance space in Hong Kong -- Appendix -- Bibliography -- Index.
Keywords: Human geography; Architecture -- History; Sociology, Urban; Human Geography; Architectural History and Theory; Urban Sociology